Respuesta :
Answer:
27
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Step-by-step explanation:
Step 1: Define
3 - 6(z - 2)
z = -2
Step 2: Evaluate
- Substitute in z: 3 - 6(-2 - 2)
- (Parenthesis) Subtract: 3 - 6(-4)
- Multiply: 3 + 24
- Add: 27
Given :
- z = - 2
To Find :
- 3 - 6(z - 2) = ?
Solution :
By substituting value of z = - 2 in 3 - 6(z - 2), we get :
[tex] \tt : \implies 3 - 6(z - 2) = 3 - 6((-2) - 2)[/tex]
[tex] \tt : \implies 3 - 6(z - 2) = 3 - 6(-2 - 2)[/tex]
[tex] \tt : \implies 3 - 6(z - 2) = 3 - 6(- 4)[/tex]
[tex] \tt : \implies 3 - 6(z - 2) = 3 + 24[/tex]
[tex] \tt : \implies 3 - 6(z - 2) = 27[/tex]
[tex] \large \underline{\boxed{\bf{ 3 - 6(z - 2) = 27}}}[/tex]
Hence, value of 3 - 6(z - 2) = 27.